Supervisi Akademik Berbasis Coaching Sebagai Strategi Transformasional: Peran Mediasi Work Engagement dalam Meningkatkan Kinerja Guru - Renalda Siswadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Academic supervision is an important instrument in improving the quality of learning and teacher professionalism. However, the implementation of supervision in various educational institutions still tends to be administrative and evaluative in nature, so it has not been optimal in supporting the development of teachers’ competencies. This article aims to examine coaching-based academic supervision as a transformational strategy for improving teacher performance through the mediating role of work engagement. This study employs a literature review method by analyzing various scientific literatures related to academic supervision, coaching, work engagement, and teacher performance. The findings indicate that the coaching approach is capable of transforming the paradigm of supervision from administrative control into a reflective, collaborative, and humanistic developmental process. Through observation, feedback, reflection, and professional development follow-up, teachers are encouraged to enhance self-awareness and continuously develop their competencies. In addition, work engagement, characterized by vigor, dedication, and absorption, functions as a psychological mechanism that strengthens the influence of supervision on improving teacher performance. Therefore, coaching-based academic supervision has the potential to become an effective strategy for building a culture of professional learning and improving the quality of education.